A Heat and Power Pinch for Process Integration targeting in hybrid energy systems. (1st June 2021) - Wang, Bohong; Klemeš, Jiří Jaromír; Gai, Limei; Varbanov, Petar Sabev; Liang, Yongtu
Abstract: Hybrid energy systems have been widely used for residential and industrial purposes. In this system, the total energy requirement of each unit can be met with heat and electricity. Pinch Analysis becomes a widely used tool for Process Integration, and using Pinch Analysis for Heat Integration is well-established. However, for the combined heat and power system, the theory and the corresponding tool deserve some more development. This paper extended the Pinch Analysis concept and proposed a Heat and Power Pinch Analysis to target the amount of heat that should be recovered from the hybrid energy system. Heat and Power Composite Curve (HPCC) is developed to visualise the total energy and the separated heat and power (electricity) requirement of a hybrid energy system in a working time period. The amount of outsourced electricity that should be purchased, and stored electricity at the startup period, and the extra electricity generated by the system at the end of the working period can be demonstrated. A case is studied to illustrate the steps of using this tool, two scenarios are discussed, and the targets are shown. Highlights: A novel extension of Pinch Analysis for the hybrid heating and power system. Targeting the required heat and power to meet the total energy demand. A novel Heat and Power Composite Curve (HPCC) to visualise the targeting. A case is studied to demonstrate the new tool.